A case of diencephalic syndrome presenting with isolated lipodystrophy. Issue 4 (October 2018) - McDermott, John H.; Harris, Julie; Fédée, Joanne; Skae, Mars; Semple, Robert; Douzgou, Sofia
Abstract : Diencephalic syndrome is a disorder characterized by severe emaciation during childhood. The rarity of the disorder coupled with nonspecific symptomology means that there is often a protracted diagnostic journey. Here, we report a child who was referred to a clinical genetics service for investigation of lipodystrophy and failure to thrive. A broad range of genetic differential diagnoses were considered and investigated before a mass lesion was identified in the hypothalamus, confirming diencephalic syndrome. In the context of this case, we consider the relevant differentials and appropriate workup of a child with lipodystrophy presenting to a genetics service. This report also highlights the importance of considering diencephalic syndrome in cases such as this.